Spatial distribution of damage by Heilipus lauri (Coleoptera: Curculionidae) and Stenoma catenifer (Lepidoptera: Elachistidae) on avocado Persea americana cv. Hass - Zapata Calero, Juan Camilo; Carabali Muñoz, Arturo; Arango Londoño, David (Revista Colombiana de Entomología, 2025)
Determining the spatial distribution of populations of Heilipus lauri and Stenoma catenifer, insects of economic and quarantine importance in avocado, is a useful information for designing and implementing integrated pest management plans. Aggregate spatial distribution is considered one of the most common patterns in nature, however, it has not been documented for these insect pest species. We propose through spatial statistical methods the analysis of data from periodic monitoring where the number of fruits with damage (FWD) caused by the two insect pests was recorded. The study was conducted between 2019-2020 in four commercial orchards of avocado cv. Hass in the department of Cauca, Colombia. A sampling design was established based on the recognition of damage on previously geopositioned trees. The spatial distribution was determined through Taylorʼs power law and Ripleyʼs K function. Taylorʼs aggregation coefficient (b) was 1.47 and 1.22 for H. lauri and S. catenifer, respectively, indicating aggregation. Ripley’s K function identified aggregation points of FWD in a radius range of 3-35 meters, with the aggregation sites being consistent across the two productive cycles. The damage was mapped indicating aggregation sites that will allow the implementation of management strategies for quarantine importance insect pests of avocado in specific sites of the crop, showing the precise location of the greatest concentration of damage and populations of H. lauri and S. catenifer.